Income Inequality and Violent Crime : Evidence from Mexico’s Drug War - Enamorado, Ted; López-Calva, Luis F.; Rodríguez-Castelán, Carlos; Winkler, Hernán (Elsevier, 2016)
The goal of this paper is to examine the effect of inequality on crime rates in a unique context, Mexico's drug war. The analysis exploits an original dataset containing inequality and crime statistics on more than 2000 Mexican municipalities over a 20-year period. To uncover the causal effect of inequality on crime, we use an instrumental variable for the Gini coefficient that combines the initial income distribution at the municipality level with national trends. Our estimates indicate that a one-point increment in the Gini coefficient between 2007 and 2010 translates into an increase of more that 36% in the number of drug-related homicides per 100,000 inhabitants. The fact that the effect found during the drug war is substantially greater is likely caused by the rise in rents to be extracted through crime and an expansion in the employment opportunities in the illegal sector through the proliferation of drug trafficking organizations (DTOs), accompanied by a decline in legal job opportunities and a reduction in the probability of being caught given the resource constraints faced by the law enforcement system. Combined, the latter factors made the expected benefits of criminal activity shift in a socially undesirable direction after 2007.